Matrix Solid-Phase Dispersion Coupled with HPLC-UV for Simultaneous Extraction, Purification and Determination of Six Lignans in Schisandra chinensis Fruits. (16th June 2021) - Song, Haiyan; Chang, Kejian; Zhang, Liang; Zhu, Wenbo; Li, Yingying; Hu, Haobin; Zhang, Xiaojuan; Xi, Yongfeng; Li, Lu
Abstract: An efficient method for simultaneous extraction, purification and determination of six lignans in Schisandra chinensis Baill was developed by employing matrix solid-phase dispersion (MSPD) extraction followed by HPLC-UV determination analysis. Several sorbent and desorption solvent that affected the extraction yield of lignans were investigated; neutral alumina and absolute ethanol were selected as the best dispersing material and desorption agent, respectively. Other extraction conditions for MSPD were optimized as follows: 1:2 of S. chinensis raw material to neutral aluminum oxide mass ratio, 1:30 (g/mL) of sample to absolute ethanol, 2.5 h of desorption time and 50°C of desorption temperature. Under the above conditions, the total extraction yield for six lignans have reached (16.99 ± 0.33) x 10 3 mg/kg with a higher content of 6.88 ± 0.25% in the extracts. Comparative studies were explored by conducting other six extraction approaches including Soxhlet extraction, heat reflux extraction, smashing tissue extraction, microwave-assisted extraction, ultrasonic-assisted extraction and ultrasonic-microwave synergistic extraction. Results showed MSPD technique not only improved the extraction yield, but also improved the purity of lignans, it can be generalized to more extraction of natural compounds. In addition, the validated HPLC-UV method had been successfully applied to analysis of lignans from 10 real S. chinensis samples.